Statins nanocrystal as well as preparation method and application thereof - LUO TENGSHUO; ZHOU JING'E; DING NANJIN; YAN ZHIQIANG; LUO SHENGGEN (2021)
The invention provides a statins nanocrystal as well as a preparation method and application thereof. The statins nanocrystal is mainly prepared from statins, a stabilizer and a freeze-drying protective additive as raw materials; and the weight ratio of the statins to the stabilizing agent to the freeze-drying protective agent is (1-10): (2-12): (0-40). The statins nanocrystal has the following technical effects that compared with statins free drugs, the statins nanocrystal shows that the blood vessel density at a tissue ischemic part is remarkably increased, particularly, the accumulation in the lung is increased, the lung blood vessel density is enhanced, and the statins nanocrystal has a remarkable curative effect on treating tissue ischemic diseases and can increase the blood vessel density of ischemic tissues and dredge blood vessels. 本发明提供了一种他汀类药物纳米晶及其制备方法和用途。本发明的他汀类药物的纳米晶，主要由他汀类药物、稳定剂和冻干保护剂为原料制成；所述的他汀类药物、稳定剂、冻干保护剂重量的比例为(1～10)：(2～12)：(0～40)。本发明具有如下技术效果：本发明的他汀类药物纳米晶，相对于他汀类游离药物，显示出在组织缺血部位的血管密度显著增加，特别是增加了在